Engagement of α3β1 and α2β1 integrins by hypervirulent Streptococcus agalactiae in invasion of polarized enterocytes - De Gaetano, Giuseppe Valerio; Lentini, Germana; Coppolino, Francesco; Famà, Agata; Pietrocola, Giampiero; Beninati, Concetta (Frontiers in Microbiology, 2024)
The gut represents an important site of colonization of the commensal bacterium Streptococcus agalactiae (group B Streptococcus or GBS), which can also behave as a deadly pathogen in neonates and adults. Invasion of the intestinal epithelial barrier is likely a crucial step in the pathogenesis of neonatal infections caused by GBS belonging to clonal complex 17 (CC17). We have previously shown that the prototypical CC17 BM110 strain invades polarized enterocyte-like cells through their lateral surfaces using an endocytic pathway. By analyzing the cellular distribution of putative GBS receptors in human enterocyte-like Caco-2 cells, we find here that the alpha 3 (α3) and alpha 2 (α2) integrin subunits are selectively expressed on lateral enterocyte surfaces at equatorial and parabasal levels along the vertical axis of polarized cells, in an area corresponding to GBS entry sites. The α3β1 and α2β1 integrins were not readily accessible in fully differentiated Caco-2 monolayers but could be exposed to specific antibodies after weakening of intercellular junctions in calcium-free media. Under these conditions, anti-α3β1 and anti-α2β1 antibodies significantly reduced GBS adhesion to and invasion of enterocytes. After endocytosis, α3β1 and α2β1 integrins localized to areas of actin remodeling around GBS containing vacuoles. Taken together, these data indicate that GBS can invade enterocytes by binding to α3β1 and α2β1 integrins on the lateral membrane of polarized enterocytes, resulting in cytoskeletal remodeling and bacterial internalization. Blocking integrins might represent a viable strategy to prevent GBS invasion of gut epithelial tissues.